Aerospace engineering training: universities experience; MATEC Web of Conferences; Vol. 48 : Space Engineering - Mertins K. V. Kseniya Viktorovna; Ivanova V. S. Veronika Sergeevna; Natalinova N. M. Nataliya Mikhailovna; Alexandrova M. A. Mariya Aleksandrovna (Practice-oriented Approach to the Specialists Training in the Aerospace Industry, 2016)
Title screen